1991
DOI: 10.1111/j.1439-0418.1991.tb01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral response of Heliothis armigera Hb. (Lep., Noctuidae) moths on a synthetic chickpea (Cicer arietinum L.) kairomone

Abstract: The synthetic chickpea kairomone composed of pentan-1 -01, (+)-A-3-carene, D,L-a-pinene and m crene, was tested with Hehothis armigera moths under long distance and short range conditions in a iight tunnel. Under both conditions it is attractive to mated, egg laying moths, more with all its four components than with pentan-1-01 or with the terpenes only, both of which induce the same attractivity. Upwind orientation of the moths is demonstrated near the source by an increased turning and by zigzag flights unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
1
12
0
1
Order By: Relevance
“…of both sexes, being attracted to crude extracts or chemicals derived from plants, either alone or in combination with a pheromone (e.g. Cantelo and Jacobson 1979;Haynes et al 1991;Rembold et al 1991;Tingle and Mitchell 1992;Kvedaras et al 2007;Shen et al 2009). Several studies have shown that plant volatiles can synergize pheromones, when the two types of semiochemicals are presented in the same trap.…”
Section: Discussionmentioning
confidence: 99%
“…of both sexes, being attracted to crude extracts or chemicals derived from plants, either alone or in combination with a pheromone (e.g. Cantelo and Jacobson 1979;Haynes et al 1991;Rembold et al 1991;Tingle and Mitchell 1992;Kvedaras et al 2007;Shen et al 2009). Several studies have shown that plant volatiles can synergize pheromones, when the two types of semiochemicals are presented in the same trap.…”
Section: Discussionmentioning
confidence: 99%
“…For H. armigera, myrcene, Z-β-ocimene and racemic linalool have been found attractive when presented as constituents in synthetic blends (Rembold et al 1991;Bruce & Cork 2001). All plant odorants found to activate the olfactory RNs in this study are common secondary metabolites of many plants, but no odorant is present in all plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Extracts from pigeon pea, Cajanus cajan , were shown to be attractive to H. armigera moths (Rembold & Tober 1987; Hartlieb & Rembold 1996). Rembold et al. (1991) demonstrated the attractiveness of a synthetic chickpea ( Cicer arietinum ) kairomone to H. armigera moths in laboratory and field experiments.…”
Section: Introductionmentioning
confidence: 99%